ANALISIS PENGARUH FOREIGN DIRECT INVESTMENT, URBAN POPULATION, TPAK, DAN PERTUMBUHAN EKONOMI TERHADAP UNEMPLOYMENT RATE DI ASEAN - Rachel Meylani Situmorang; Indra Maipita (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2026)
This study aims to analyze the influence of Foreign Direct Investment, Urban Population, Labor Force Participation Rate (TPAK), and Economic Growth on Unemployment Rate in ASEAN. The analysis employs the scope of member countries of the Association of Southeast Asian Nations (ASEAN) as the object of this study. This research utilizes a quantitative method with secondary data analysis as the data collection technique. The data were obtained from various official institutions such as World Bank Data, BPS (Central Statistics Agency), as well as other additional sources. Furthermore, this study integrates supporting references in the form of scientific publications to deepen and complement the analysis conducted. The analysis process was conducted using panel data regression analysis supported by Eviews version 12 software. The results indicate that FDI has a positive and insignificant influence on Unemployment Rate in ASEAN throughout the 2015-2024 period. Urban Population demonstrates a negative and significant influence on Unemployment Rate in ASEAN throughout the 2015-2024 period. TPAK has a negative and significant influence on Unemployment Rate in ASEAN throughout the 2015-2024 period. Economic Growth shows a positive and insignificant influence on Unemployment Rate in ASEAN throughout the 2015-2024 period. Simultaneously, Foreign Direct Investment, Urban Population, TPAK, and Economic Growth have a significant influence on Unemployment Rate in ASEAN from 2015-2024 with a contribution of 85.65%, while the remaining 14.35% is explained by other factors outside the scope of this study